Quercetin 3, 3', 4', 5, 7-O- pentasulfate (QPS): A novel activator of protein disulfide isomerase - Abdul Burhan Khan; Neha Gupta; Qudsia Rashid; Irshad Ahmad; Shadabi Bano; Urfi Siddiqui; Mohammad Abid; Mohamad Aman Jairajpuri (Elsevier, 2020)
Aims: Design and synthesis of a novel 3, 3', 4', 5, 7-O- pentasulfated Quercetin (QPS) as an activator of protein disulfide isomerase (PDI). Main Methods: Based on an in silico analysis we show that QPS binds to a and b domain of PDI (−7.4 kcal/mol) unlike PDI inhibitor quercetin 3-rutinoside (Q3R) that binds at substrate-binding domain b (−8.0 kcal/mol). QPS was synthesized and its structure validated using a combination of FTIR, NMR and mass spectral studies. Surprisingly, unlike Q3R QPS is shown to enhance the activity of purified recombinant PDI. Fluorometric and circular dichroism analysis showed that QPS binds to a unique site on PDI with marginal variations in its secondary structure. Key Findings: Hypersulfation of quercetin reverses its inhibitory effect on PDI as addition of exogenous PDI and QPS in human plasma showed increase in rate of coagulation, unlike Q3R which shows a decrease. Significance: The results indicate QPS to be a novel enhancer of PDI activity that can influence the coagulation rates in plasma. QPS has therapeutic potential to control bleeding.